BHLHE40 contributes to allergic asthma progression in mice through NRTN downregulation in macrophages - Bing Dai; Li Chen; Xiaowen Li; Qianlan Zhou; Qinzhen Zhang; Lina Han; Wenxin Shen; Qing Chang; Yuhong Zhao; Si Liu; Lishen Shan (Communications Biology)
Abstract Alternatively activated M2-like macrophages have a profound impact on asthma pathogenesis. Basic Helix-Loop-Helix Family Member E40 (BHLHE40), a dimeric transcriptional factor, plays a key regulation in macrophage functions. Here we show that ovalbumin (OVA)-challenged mice exhibited greater expression of BHLHE40 in lung tissues. Bhlhe40 knockdown reduced the pulmonary lesions and allergy-induced inflammation in asthmatic mice. Moreover, an inhibitory effect of Bhlhe40 knockdown on alternative activation was observed in vivo and in vitro. We show a downstream target Neurturin (Nrtn) of Bhlhe40. Dual luciferase assay and ChIP-qPCR assay indicated that BHLHE40 bound to Nrtn promoter and reduced its transcriptional activity. Simultaneous knockdown of Bhlhe40 and Nrtn recovered the alternative activation of macrophages and rescued the OVA-elicited asthma phenotype. NRTN downregulation offset the alleviative effects of Bhlhe40 knockdown on asthma. This study demonstrates that BHLHE40 promotes allergic asthma, and contributes to the alternative activation of macrophages in asthma by inhibiting Nrtn transcription.